2002
DOI: 10.1034/j.1399-5618.2002.09073.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifamily psychoeducation groups (MFPG) for families of children with bipolar disorder

Abstract: While BPD families enter treatment with more impaired children and more extensive treatment histories, both BPD and MDD/DD families benefit from intervention. The clinical issues concerning combining families of children with bipolar and depressive spectrum illnesses in groups are discussed. Clinical impressions suggest that such combinations are clinically feasible and potentially beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 36 publications
1
102
1
5
Order By: Relevance
“…Previous research provides support for the efficacy of adjunctive family-focused psychoeducation and skills-based interventions for youth with BPSD, including psychoeducational psychotherapy (PEP), family-focused treatment, and child-and family-focused cognitive behavioral therapy West et al 2014). PEP has the strongest evidence base for treating children £12 years of age with BPSD (Fristad et al 2002(Fristad et al , 2003Fristad 2006;Fristad et al 2009;Mendenhall et al 2009;Fristad and MacPherson 2014). Key goals of PEP are to provide psychoeducation about mood disorders and treatments, provide social support, and build skills in symptom management, emotion regulation, problem solving and communication.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research provides support for the efficacy of adjunctive family-focused psychoeducation and skills-based interventions for youth with BPSD, including psychoeducational psychotherapy (PEP), family-focused treatment, and child-and family-focused cognitive behavioral therapy West et al 2014). PEP has the strongest evidence base for treating children £12 years of age with BPSD (Fristad et al 2002(Fristad et al , 2003Fristad 2006;Fristad et al 2009;Mendenhall et al 2009;Fristad and MacPherson 2014). Key goals of PEP are to provide psychoeducation about mood disorders and treatments, provide social support, and build skills in symptom management, emotion regulation, problem solving and communication.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar disso, os estudos demonstraram eficácia em alguns aspectos, tais como, a redução dos sintomas do TB (e.g., Miklowitz et al, 2008;Fristad et al, 2009;Fristad, 2006;Fristad et al, 2002;Miklowitz et al, 2004;Miklowitz et al, 2011), comportamentos mais adequados dos pais frente ao TB de seus filhos (e.g., Fristad et al, 2003;Fristad, 2006); melhora do relacionamento familiar (e.g., Fristad, 2006;Fristad et al, 2002); ganho de experiência, aumento do conhecimento dos pais em relação à doença e aumento do apoio familiar e social (e.g., Fristad et al, 2003;Fristad et al, 2002). Estes resultados se mantiveram após o follow-up.…”
Section: Discussionunclassified
“…Multi-family psychoeducational group (MFPG) therapy involves eight 90-minute sessions for parents from a number of families with concurrent sessions for children [133]. The curriculum for MFPG is similar to that of the RAINBOW programme, but the group format creates a context within which parents and children gain social support from other families with similar difficulties.…”
Section: Multi-family Psychoeducational Groupsmentioning
confidence: 99%
“…They also learn a variety of CBT strategies for combating to help them with this process. In a trial of MFPG involving 16 bipolar cases and 19 cases with unipolar depression, Fristad et al [133] found that after treatment and at 4 months follow-up families of both groups showed significant gains in knowledge, skills, support and positive attitudes towards treatment.…”
Section: Multi-family Psychoeducational Groupsmentioning
confidence: 99%